1920
DOI: 10.2307/2341080
|View full text |Cite
|
Sign up to set email alerts
|

An Inquiry into the Nature of Frequency Distributions Representative of Multiple Happenings with Particular Reference to the Occurrence of Multiple Attacks of Disease or of Repeated Accidents

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
276
0

Year Published

1935
1935
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 751 publications
(296 citation statements)
references
References 0 publications
5
276
0
Order By: Relevance
“…Other assumptions are possible, but do not reduce to closed form, and thus require more complicated estimation procedures (see Schoenberg, 1985). Greenwood and Yule (1920) first derived the new distribution, called the negative binomial, by adding this additional first principle (hi following a gamma distribution) to the initial four with the following procedure. First, derive the joint distribution ifi) of Yi and Xi (both now random variables) using the basic rule for conditional probability…”
Section: Modeling Event Counts With Overdispersionmentioning
confidence: 99%
“…Other assumptions are possible, but do not reduce to closed form, and thus require more complicated estimation procedures (see Schoenberg, 1985). Greenwood and Yule (1920) first derived the new distribution, called the negative binomial, by adding this additional first principle (hi following a gamma distribution) to the initial four with the following procedure. First, derive the joint distribution ifi) of Yi and Xi (both now random variables) using the basic rule for conditional probability…”
Section: Modeling Event Counts With Overdispersionmentioning
confidence: 99%
“…Heterogeneity in connection with Poisson processes was in fact studied as early as 1920 by Greenwood and Yule [27], who used a compound Poisson distribution. Later, Maguire, Pearson and Wynn [50], studying occurrences of industrial accidents, showed how Laplace transforms enter general expressions for resulting distributions of intervals and counts.…”
Section: Unobserved Heterogeneity In Repairable Systemsmentioning
confidence: 99%
“…It is well known that the parameter in a Poisson distribution is considered to be a gamma variate in the famous article by Greenwood and Yule (1920). Skellam (1948) derived a probability distribution from the binomial distribution by regarding the probability of success as a beta variable between sets of trials.…”
Section: Introductionmentioning
confidence: 99%